Nonlinear optomechanical measurement of mechanical motion - G. A. Brawley (Nature Portfolio, 2016)
The measurement of non-linear mechanical degrees-of-freedom provides a pathway to explore quantum behaviour at macroscopic scales. Here, Brawley et al.report the observation of displacement-squared thermal motion of a micro-mechanical resonator by exploiting the intrinsic non-linearity of the radiation-pressure interaction.